Implementation of a Fun School Movement Program in Singkawang City - Azizah Azizah; Dede Sri Kartini; Rahman Mulyawan (Dinasti Publisher, 2025)
The objective of this study is to describe and analyze the implementation of the seven-steps of fun school movement in Singkawang City as a means to improve the quality of basic education in Singkawang City. The analysis was conducted using Merilee S. Grindle's policy implementation theory, which includes content and context variables. This study employed a descriptive qualitative method with an inductive approach. Data collection techniques included observation, interviews, and document studies. The results showed that the the seven-step fun school movement has accommodated the interests of all target groups, namely students, teachers, principals, parents, and the community. This program provides academic, social, and health benefits that are felt directly, fairly, and evenly. The movement also succeeded in encouraging positive changes in the cognitive, affective, and psychomotor aspects of the target groups, thus creating a more positive and student-centered school culture. However, the resources, including funding, human resources, and infrastructure, are still inadequate and need improvement. The implementation of this program involved various actors with different powers, interests, and strategies, but in general, it showed high commitment and support. The characteristics of the implementing agencies, such as a flexible organizational structure, a responsive organizational culture, and strong leadership, also supported the successful implementation. Based on the results of the study, it is recommended that the Singkawang City Government increase support and socialization of the program, as well as strengthen regulations. Schools are encouraged to continue to innovate and involve the entire school community. Parents and communities are expected to improve understanding and participation in the program.